Genetic analysis of p38 MAP kinases in myogenesis: fundamental role of p38α in abrogating myoblast proliferation - Perdiguero, Eusebio (Nature Publishing Group, 2007)
The p38 mitogen-activated protein kinase (MAPK) pathway plays a critical role in skeletal muscle differentiation. However, the relative contribution of the four p38 MAPKs (p38α, p38β, p38γ and p38δ) to this process is unknown. Here we show that myoblasts lacking p38α, but not those lacking p38β or p38δ, are unable to differentiate and form multinucleated myotubes, whereas p38γ-deficient myoblasts exhibit an attenuated fusion capacity. The defective myogenesis in the absence of p38α is caused by delayed cell-cycle exit and continuous proliferation in differentiation-promoting conditions. Indeed, activation of JNK/cJun was enhanced in p38α-deficient myoblasts leading to increased cyclin D1 transcription, whereas inhibition of JNK activity rescued the proliferation phenotype. Thus, p38α controls myogenesis by antagonizing the activation of the JNK proliferation-promoting pathway, before its direct effect on muscle differentiation-specific gene transcription. More importantly, in agreement with the defective myogenesis of cultured p38α(Δ/Δ) myoblasts, neonatal muscle deficient in p38α shows cellular hyperproliferation and delayed maturation. This study provides novel evidence of a fundamental role of p38α in muscle formation in vitro and in vivo.